Perbedaan Display Toko Offline dan Toko Online Untuk Produk Pakaian Wanita - Heni Iswati; Nina Maharani (Universitas Islam Bandung, 2019)
Along with the development of technology, the way to buy clothing products has also shifted. Purchases through an offline store where consumers come directly to the store to buy, and through online stores where consumers can shop through gadgets anytime and anywhere. The purpose of this study was to determine the perceptions and differences of offline store and online stores displays. The method used was descriptive and quantitative about 400 respondents in the city of Bandung. Whereas previously the respondents had also accessed or purchased women's clothing products through offline and online stores. Based on the results obtained there are differences between offline and online store displays. In terms of practicality in buying and time, online stores get a good response, while in the information and quality of products, online stores get less response. Regarding prices, there is no significant difference between offline and online stores. Although there are differences between offline and online stores, they do not turn off the market and the sales system that is carried out between the two shops. Because these differences make the two stores unique. But overall the online store is more in demand because of its ease when accessed by consumers. Keywords: offline shop, online shop, display